Morocco : Second Review under the Precautionary and Liquidity Line. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper highlights Morocco's Second Review Under the Precautionary and Liquidity Line. The IMF report analyzes that the 2012 fiscal outcome entailed a significant slippage from the authorities' target and exposed vulnerabilities in the budget framework. Core inflation has remained low while the unemployment rate remained about 9 percent. After worsening in 2012, the current account has been improving in 2013, while reserves have stabilized at about four months of imports. Liquidity conditions have remained tight, and credit growth has continued to decelerate, driven by both supply and demand factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet